O tehnološkem predvidevanju - Indihar, Stane (Naše gospodarstvo, 2007)
Technological forecasting (TF) is an effective tool in decision making at the national level or at lower levels. Activities in the field of TF have provided different qualitative and quantitative methods and many examples of their application. The aim of this article is: (1) to briefly present these methods and (2) to show some applications for practical use. More emphasis is given to the Delphi method and to growth curves.
Keywords: tehnološki razvoj; inovacije; predvidevanje; metodologija; ekonomski razvoj; družbeni razvoj